2019
DOI: 10.1177/1559827619879065
|View full text |Cite
|
Sign up to set email alerts
|

A Call to Action for Intermediate and Secondary School Lifestyle Medicine Education: Instating Healthy Teen Behaviors

Abstract: Chronic diseases, previously thought to require decades of risk factors, have become increasingly prevalent in America’s youth. National Health Education Standards have been published since 1995, and yet nearly a fifth of schools fail to follow any state or national health education guidelines. Utilizing the phrase “lifestyle medicine” in childhood would elevate the importance and standardization of the core health guidelines. Several independent pilot programs taught by undergraduate and medical student volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…ACLM members have been working to make this a reality throughout the United States for the past four years. 11,12 ACLM has a full teen curriculum available to members that can be used in middle school or high school. A Teen Lifestyle Medicine Handbook, 12 decks of PowerPoint Slides, and a Teacher's manual to help empower teachers to use the curriculum.…”
Section: Lifestyle Medicine Education For Health Professionals and Th...mentioning
confidence: 99%
“…ACLM members have been working to make this a reality throughout the United States for the past four years. 11,12 ACLM has a full teen curriculum available to members that can be used in middle school or high school. A Teen Lifestyle Medicine Handbook, 12 decks of PowerPoint Slides, and a Teacher's manual to help empower teachers to use the curriculum.…”
Section: Lifestyle Medicine Education For Health Professionals and Th...mentioning
confidence: 99%
“…70 In fact, lifestyle medicine experts have argued that introduction to lifestyle principles and practices may be beneficial as early as middle school. [70][71][72] Such education can also be utilized to help students appreciate the role of mental and behavioral health in lifestyle medicine approaches and general health. Appreciating the foundational role of lifestyle medicine as both primary treatment, and adjunct to traditional treatment, particularly in the case of mental health, is incredibly important for future generations of providers.…”
Section: Leveraging (Early) Educationmentioning
confidence: 99%
“…They also learned how to use sleep as a tool for boosting performance in the classroom. 6 In addition to this, they also found that when students were provided with evidenced based approaches to health lifestyles, they we able to better understand the power and importance of lifestyle medicine. 6…”
mentioning
confidence: 90%
“…6 In addition to this, they also found that when students were provided with evidenced based approaches to health lifestyles, they we able to better understand the power and importance of lifestyle medicine. 6 As epidemiological studies have demonstrated that early childhood maltreatment can have an impact on health and emotional wellbeing, 10 combined with the large body of research highlighting the importance of early lifestyle medicine intervention, we at Edison Young People are launching a lifestyle medicine programme across some of our residential homes, in the hope to assist our CYP in developing healthy daily habits to improve their short-term and long-term health, along with increasing their quality of life. The program is overseen by Dr Beth Frates and Clinical Lead Stelios Kiosses and run by our assistant psychologist Abbie Garrett who is also responsible for introducing lifestyle medicine to our CYP and the care staff working with the CYP.…”
mentioning
confidence: 90%
See 1 more Smart Citation